Analysis of The Effect Locus of Control and Leadership Style on Auditor Performance with Job Satisfaction as A Mediation (Study at Audit Board of the Republic of Indonesia Representative of East Java Province) - Tri Maryanti; Endah Susilowati (Nusantara Science and Technology Proceedings, 2020)
Locus of control is an indicator that affects job satisfaction and performance. The aspects that are assessed on the performance of the Audit Board auditors cannot be separated from the locus of control, leadership style, and job satisfaction. All these aspects are assessed proportionally by giving a more dominant weight to work performance without neglecting the aspects of work behavior. The selection of Audit Board Representative of East Java Province auditors cannot be separated from the locus of control and leadership style to create auditor performance which is mediated by job satisfaction in East Java, both because of internal and external factors. The purpose of this study is to analyze the effect of locus of control on job satisfaction of auditors at Audit Board Representatives of East Java Province, analyze the effect of job satisfaction on auditor performance, analyze the effect of locus of control on auditor performance, analyze the effect of leadership style on auditor performance, analyze the effect of job satisfaction mediates locus of control on auditor performance and analyzes job satisfaction mediates leadership style on auditor performance. This research used quantitative methods, while the sampling technique is based on purposive sampling and data processing use Partial Least Square (PLS) analysis with SMART PLS software. The results show that each variable affects each of the other variables. This research contributes to Audit Board Representatives of East Java Province paying close attention to the locus of control of auditors and considering work management mechanisms that harmonize the relationship between superiors and auditors. Therefore, further research requires more diverse and in-depth interviews, as well as various respondents.